THE RELATIONSHIP BETWEEN THE LEVEL OF MATERNAL KNOWLEDGE ABOUT MP-ASI AND THE NUTRITIONAL STATUS OF BADUTA AT THE AGE OF 6-24 MONTHS IN THE WORKING AREA OF THE PADANG PANYANG HEALTH CENTRE, KUALA PESISIR DISTRICT, NAGAN RAYA REGENCY IN 2024. - Nabila Oktaviani; Nasrianti Syam; Suci Eka Putri; Sri Wahyuni Muhsin (PT. Radja Intercontinental Publishing, 2024)
A 6-month-old baby requires complementary feeding (MP-ASI) to meet nutritional needs and support growth and development. The mother's knowledge of proper MP-ASI provision influences the baby's nutritional status, including types, composition, and feeding methods. The nutrition received will directly affect the baby's growth. This study aims to analyze the relationship between maternal knowledge of MP-ASI and the nutritional status of babies aged 6-24 months in the working area of Padang Panyang Health Center, Kuala Pesisir District, Nagan Raya Regency. This quantitative study uses an analytical observational method with a cross-sectional design and Purposive Sampling technique. Ninety-three mothers with children aged 6-24 months were selected as samples. Data was collected using a questionnaire to assess maternal knowledge and anthropometric measurements to evaluate nutritional status. The data were analyzed using the Chi-Square test, showing a significant result (p=0.006, p<0.05). The results showed that 55.9% of mothers had sufficient knowledge, 34.4% had poor knowledge, and 9.7% had good knowledge. Additionally, 80.6% of babies had normal nutritional status, while 19.4% had abnormal nutritional status, indicating a strong relationship between maternal knowledge and the nutritional status of babies. Mothers with a better understanding of MP-ASI provision tend to have children with better nutritional status.